Literature Review: Akuntansi Forensik Untuk Deteksi Korupsi - Bobby Hartadhy Toeweh (Studi Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This study aims to be able to reveal whether forensic accounting can and is effectively used to detect corruption in the management and use of budget funds for handling the Covid-19 pandemic in Regional Governments, especially the allocation of large funds used for the procurement of goods and services that are disposable. This is important, because the criminal act of corruption is an extraordinary crime, so it is necessary to have extraordinary tools to be able to detect and reveal the crime. Method: This study uses a descriptive qualitative method with an emphasis on literature review, namely by observing and analyzing all information related to the research topic, and combined with previous research in order to explain the phenomena that will occur. Result: The results show that forensic accounting can be used and effective to detect and reveal fraud in the management and use of the budget for handling the Covid-19 pandemic in the Regional Government through review activities and the implementation of investigative audits. Limitations: This research is limited to the effectiveness of forensic accounting for detecting corruption in the use of funds for handling Covid-19 in the Regions and is limited to the role of the Government Internal Supervisory Apparatus (APIP) in the Regions in utilizing forensic accounting in audit activities. Contribution: this research can be a reference for further research related to the influence of forensic accounting in the implementation of audits in the regions by the Government Internal Supervisory Apparatus (APIP).